HEALTH PROGRAM IN SCHOOLS: FITNESS CONDITION EVALUATION OF JOSÉ MARIA ALKMIN BELO HORIZONTE MUNICIPAL SCHOOL STUDENTS (Fiep Bulletin - online, 2015)
The present study aimed to assess the health of students assisted by the School Health Program / Training Program by Work (PSE- Propet / UFMG) in the area of Physical Education. The evaluation was performed through indicators of body growth and physical fitness and health, using the instrument - Design Sport Brazil PROESP - Br (2012). The sample consisted of 107 students from the Escola Municipal José Maria Alckmin aged between seven and fourteen. The tests were conducted at the school. For the evaluation of the indicators of physical fitness, tests related to the pattern of body growth (weight and height) and physical fitness for health (body mass index, race / 6-minute walk, flexibility and abdominal strength) were used. Data was collected according to standard tests developed and launched by the Program Classification PROESP-Br (2012) and processed using descriptive statistics (mean and standard deviation). After analysis of normality (Shapiro-Wilk test) and homoscedasticity (Levene), we used one-way ANOVA One-way, Kruskal Wallis test (for comparison between ages) and Mann Whitney U Test yourself (for comparison between genders), as well as post hoc Bonferroni multiple pairwise comparisons when significant differences were identified when comparing the ages Nível 5% significance for all analyzes, using SPSS 20.0 software. The results of measurements of BMI values in children demonstrate a healthy zone, but the other tests (aerobic endurance, abdominal strength and flexibility) resulted in amounts considered as a risk to health. This study, aiming to assess the health of students assisted by PSE / PROPET / UFMG in the area of Physical Education, indicates that physical fitness in students of school Municipal José Maria Alckmin is poor, so it is necessary to think of better public health policies and education that are effective for physical and maturational development of these children.
Keywords: health; fitness; school health.